1998
DOI: 10.1038/sj.pcan.4500221
|View full text |Cite
|
Sign up to set email alerts
|

Components of the metabolic syndrome—risk factors for the development of benign prostatic hyperplasia

Abstract: The purpose of the present study was to perform a BPH risk factor analysis in men, relating the prostate gland volume to components of the metabolic syndrome and to identify clues to the etiology of BPH.Our material comprised a consecutive series of 158 patients with lower urinary tract symptoms with or without manifestations of the metabolic syndrome. In this group, the measured volume of the prostate was related consecutively to potential risk factors. The diagnoses atherosclerosis, non-insulin-dependent dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
226
3
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(255 citation statements)
references
References 11 publications
17
226
3
9
Order By: Relevance
“…48 Several studies also have reported hyperinsulenemia or the metabolic syndrome associated with higher PSA levels, but this was believed to be mediated through the effects of obesity and insulin on increased prostate volume and benign prostatic hyperplasia. [50][51][52][53] Thus, while the mechanisms linking C-peptide or HbA1c to PSA requires further investigation, the observed inverse relationships in this study are generally consistent with the previously reported inverse relationship between testosterone and insulin.…”
Section: Discussionsupporting
confidence: 91%
“…48 Several studies also have reported hyperinsulenemia or the metabolic syndrome associated with higher PSA levels, but this was believed to be mediated through the effects of obesity and insulin on increased prostate volume and benign prostatic hyperplasia. [50][51][52][53] Thus, while the mechanisms linking C-peptide or HbA1c to PSA requires further investigation, the observed inverse relationships in this study are generally consistent with the previously reported inverse relationship between testosterone and insulin.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation for an association between obesity or height and prostate volume are consistent with several studies evaluating prostate size or clinical BPH. 4,6,9,11 For example, Freedland et al 9 reported prostate weight was about 5 g greater among prostate cancer patients (70.2%…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of obesity and abdominal adipose deposition also increases with age 2,3 and changes in steroid hormone metabolism, insulin regulation, or SHBG levels associated with aging and prostatic enlargement may be accelerated with obesity. 3 However, results from research investigating the association between body mass index (BMI) 4,5 or estimated visceral adiposity 4,6 and clinically diagnosed BPH are inconsistent. Investigation of prostate volume or prostate weight may avoid subjective diagnostic criteria associated with a BPH diagnosis, and several recent studies reported BMI associated with prostate volume 7,8 and prostate weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have also all been shown to be risk factors for the development of ED. [45][46][47][48] AH is another component of the metabolic syndrome, involving dysregulation of parasympathetic and sympathetic tone. Penile erection is impaired by increased sympathetic tone.…”
Section: Ah and The Metabolic Syndromementioning
confidence: 99%